Pengaruh Ozon yang Dibangkitkan Melalui Reaktor Plasma Berpenghalang Dielektrik Elektroda Silinder Spiral Terhadap Pengawetan Cabai - Saraslifah Saraslifah; Muhammad Nur; Fajar Arianto (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2016)
Research on the effects of ozone generated by the plasma reactor cylindrical spiral electrode to the shelf life of chili has been done in Plasma Physics Laboratory, Diponegoro University. This study aims to obtain optimal voltage values to produce maximum ozone. And obtaining effect of ozonation time and storage for chili quality. Ozon which used is produced by dielectric barrier discharge plasma reactor with spiral cylinder configuration. This ozon , which produced by the reactor dissolved in water for washed the chili. Chili using ozone washing is done with a variety of washing time 0,5,10,15,20,25 and 30 minutes. The chili then stored in a refrigerator at a temperature of 17 ℃ for 25 days. Characterization of the reactor showed that the greater value of the applied voltage, increased current and concentration of ozone produced. Voltage used for ozonantion is 2400 V with a concentration of ozone generated at 23.75 ppm. Ozone dissolved in water to wash the chili with dissolved ozone concentration is 1.66 ppm or 7%. From the analysis of the level of damage chili, ozonation results with lowest damage rate is at the time of treatment 15 minutes with a percentage of 8% damage to the shelf life of 25 days. From the test results of proximate preservation chili using ozone is not particularly affect the content in chili peppers that is safe to use. The longer the treatment time, reduce the amount of bacteria on pepper growing. At thetime of treatment 15 minutes colonies of fungi reduced til 50,8 % and bacteria were reduced 51.7%. It seen from the results of TPC (Total Plate Count).